2009
DOI: 10.1242/dev.032300
|View full text |Cite
|
Sign up to set email alerts
|

The sea urchin animal pole domain is a Six3-dependent neurogenic patterning center

Abstract: Two major signaling centers have been shown to control patterning of sea urchin embryos. Canonical Wnt signaling in vegetal blastomeres and Nodal signaling in presumptive oral ectoderm are necessary and sufficient to initiate patterning along the primary and secondary axes, respectively. Here we define and characterize a third patterning center, the animal pole domain(APD), which contains neurogenic ectoderm, and can oppose Wnt and Nodal signaling. The regulatory influence of the APD is normally restricted to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
131
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 105 publications
(139 citation statements)
references
References 56 publications
8
131
0
Order By: Relevance
“…Among those that were expressed in the anterior neuroectoderm (ANE) was one encoding a zinc finger-containing protein, called Z81 (Materna et al, 2006). Further studies showed that its expression in the ANE depended on Six3, a factor required for neural development (Wei et al, 2009). This gene (Z81; SPU_022242) was initially annotated as zfh-1 (Sodergren et al, 2006) and has subsequently been called Smad Interacting protein, Sip1 or SmadIP (Saudemont et al, 2010) or SpSip1 (Su et al, 2009).…”
Section: Resultsmentioning
confidence: 99%
“…Among those that were expressed in the anterior neuroectoderm (ANE) was one encoding a zinc finger-containing protein, called Z81 (Materna et al, 2006). Further studies showed that its expression in the ANE depended on Six3, a factor required for neural development (Wei et al, 2009). This gene (Z81; SPU_022242) was initially annotated as zfh-1 (Sodergren et al, 2006) and has subsequently been called Smad Interacting protein, Sip1 or SmadIP (Saudemont et al, 2010) or SpSip1 (Su et al, 2009).…”
Section: Resultsmentioning
confidence: 99%
“…A common feature is the presence of bilaterally displaced serotonin containing neurons (Bisgrove and Burke, 1986;Yaguchi and Katow 2003;Byrne et al 2006). The differentiation of the neurogenic ectoderm appears to be mediated by a core set of metazoan neural transcription factors, including the transcription factors paired-class, achaete-scute, Zic, Six-3 Poustka et al 2007;Wei et al 2009). Wei et al (2009) have identified a large set of animal pole domain regulatory genes that depend upon Six-3 expression and suggest that a gene regulatory network involving Six-3 is necessary for the differentiation of this domain.…”
Section: The Animal Pole Nervous Systemmentioning
confidence: 99%
“…The differentiation of the neurogenic ectoderm appears to be mediated by a core set of metazoan neural transcription factors, including the transcription factors paired-class, achaete-scute, Zic, Six-3 Poustka et al 2007;Wei et al 2009). Wei et al (2009) have identified a large set of animal pole domain regulatory genes that depend upon Six-3 expression and suggest that a gene regulatory network involving Six-3 is necessary for the differentiation of this domain. Neurons associated with the ciliary band also differentiate during late gastrulation (Nakajima et al 2004a).…”
Section: The Animal Pole Nervous Systemmentioning
confidence: 99%
See 2 more Smart Citations